High Availability Service dengan Multiple Master pada Kubernetes Cluster Menggunakan Virtualisasi Kernel Based Virtual Machine (KVM) - Nabila Firdha Aisyah; Muhammad Arif Fadhly Ridha (Politeknik Caltex Riau, 2022)
Servers have an important role in managing and serving requests from clients. So that high availability is needed to handle risks in server use. Cluster technology is needed, so that the server load is shared evenly. However, to run clustering, it requires the application of a method, namely the HAProxy load balancer which works by evenly distributing the traffic load to the clustered physical servers. By implementing Kernel-Based Virtual Machine (KVM) virtualization technology. In KVM virtualization there is a technology used, namely Kubernetes. From the results of this final project, the results of the High Availability testing carried out are known that the server performance with scenario 5 access experiments 20-500 users with stress testing. Parameters measured are throughput and monitoring system usage of CPU, memory according to user access load. Which is the highest value of Througput on parameter 500 clients worth 1330.6/ sec. The presence of 2 servers provides performance test results. In standby, the lowest CPU usage and memory usage occurs on the main server, which is 0.07% and 24% because there are no nodes running on top of the virtual machine. In a busy state, the lowest CPU usage occurs on the main server is 1.06% due to the division of workload on virtual machines. The lowest memory usage occurs on the main server server is 24% because there are no nodes running on top of the virtual machine.